Evaluation of Land Use System for Supporting Sustainable Development of Agriculture in Quoc Oai District, Hanoi City - Tai, Do Thi Thu; Tuan, Tran Van (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 4, 2017)
The area of agricultural land in Quoc Oai district is 9949,0 hectares, accounting for 65,83% of total area of the district. The study has identified 77 land use systems (LUS) which are based on 56 land units and 7 major land use types. The evaluation of effectiveness of ecological adaptability, economics, social and environment allows to determine major priorities/production models in agriculture such as: rice, rice-fish, fruit trees, tea, short-day plants, forest (acacia) and aquaculture. Fruit-tree model, a land use type which has a wide ecological adaptability, creating the best economic benefit (168.4 million/ha/year), was selected as the local people's priorities. This model showed lesser negative environmental impacts. The LUS evaluation process described in this paper can be applied for other districts in Hanoi where the agricultural land is still redundant. Keywords Land use system, agricultural land, Quoc Oai District References [1] Phùng Gia Hưng, Xác định cơ cấu sử dụng đất nông nghiệp hợp lý trên vùng đất bạc màu Bắc Giang, Luận án Tiến sĩ nông nghiệp, Trường Đại học Nông nghiệp Hà Nội, 2012 [2]. Đoàn Công Quỳ, Đánh giá đất đai phục vụ quy hoạch sử dụng đất nông - lâm nghiệp huyện Đại Từ, tỉnh Thái Nguyên, Tạp chí Địa chính số 4, 8/2001. [3] FAO, Land evaluation and Farming system analisys for land use planning, FAO, Rome, Italy, 1992. [4] Trần An Phong (chủ biên), Đánh giá hiện trạng sử dụng đất theo quan điểm sinh thái và phát triển lâu bền, NXB Nông nghiệp, Hà Nội, 1995. [5] Đào Châu Thu, Nguyễn Khang, Giáo trình đánh giá đất, NXB Nông nghiệp, Hà Nội, 1998. [6] Nguyễn Quang Học, Đánh giá và đề xuất sử dụng tài nguyên đất, nước phát triển nông nghiệp bền vững huyện Đông Anh, Hà Nội, 2000 [7] Nguyễn Xuân Hải, Xây dựng cơ sở dữ liệu tích hợp liên ngành đối với tài nguyên đất nông nghiệp của Hà Nội, 2012 – 2013 [8] Vũ Thị Bình, Đánh giá đất phục vụ định hướng quy hoạch nâng cao hiệu quả sử dụng đất huyện Gia Lâm, thành phố Hà Nội, Luận án Phó Tiến sĩ nông nghiệp, Trường Đại học Nông nghiệp Hà Nội,1995. [9] Nguyễn Cao Huần, Đánh giá cảnh quan theo tiếp cận kinh tế - sinh thái, NXB Đại học Quốc Gia Hà Nội, 2005. [10] Đỗ Thị Tài Thu và nnk, Ứng dụng GIS xây dựng bản đồ hệ thống sử dụng đất phục vụ công tác đánh giá đất tại huyện Quốc Oai, thành phố Hà Nội, Hội thảo GIS toàn quốc (2015) 511. [11] UBND huyện Quốc Oai, Báo cáo thống kê, kiểm kê diện tích đất đai huyện Quốc Oai, thành phố Hà Nội năm 2015, Hà Nội, 2015. [12] Handbook of Cost – Benefit Analysis, Australian Government Publishing Service, Canberra, 1992. [13] Trần Văn Tuấn, Nguyễn Cao Huần, Đỗ Thị Tài Thu và nnk, Nghiên cứu, đánh giá hệ thống sử dụng đất đai phục vụ quy hoạch sử dụng đất nông nghiệp bền vững (Nghiên cứu điểm: xã Đại Thành, huyện Quốc Oai, thành phố Hà Nội), Tạp chí Khoa học ĐHQGHN (2015).